2018
DOI: 10.1016/j.seizure.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Long-term seizure outcome in pediatric patients with focal cortical dysplasia undergoing tailored and standard surgical resections

Abstract: Focal cortical dysplasia (FCD) is the major cause of focal intractable epilepsy in childhood. Here we analyze the factors influencing the success of surgical treatment in a large cohort of children with histologically ascertained FCD. Method: A retrospective study of the effects of FCD type, surgical intervention, and age at surgery in a pediatric cohort. Results: A total of 113 patients (71 male; mean age at surgery 10.3 years; range 0-18) were analyzed; 45 had undergone lesionectomy, 42 lobectomy, 18 multi-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 36 publications
0
36
1
Order By: Relevance
“…However, it is not simple to say "the earlier, the better. " In patients with an unclear extent of EZ, or younger age with high perioperative risk, or low sensitivity of MRI, later resections may offer advantages in terms of precision of surgical-resection planning [92]. Early surgical intervention in drug-resistant epilepsy can support functional plasticity in children.…”
Section: Surgical Outcomementioning
confidence: 99%
“…However, it is not simple to say "the earlier, the better. " In patients with an unclear extent of EZ, or younger age with high perioperative risk, or low sensitivity of MRI, later resections may offer advantages in terms of precision of surgical-resection planning [92]. Early surgical intervention in drug-resistant epilepsy can support functional plasticity in children.…”
Section: Surgical Outcomementioning
confidence: 99%
“…A meta‐analysis of 36 publications (1993‐2012) comprising 1318 children with temporal and 1259 children with extratemporal resections showed seizure freedom rates (Engel class I) of 76% for temporal lobe resections and 56% for extratemporal resections (minimum follow‐up = 12 months) . A detailed study of long‐term outcome in pediatric focal cortical dysplasias was recently published . A comparison of trends between existing pediatric and adult series from different centers is difficult because of potentially divergent catchment areas and inconsistent presurgical, surgical, and postsurgical strategies and assessments.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 A detailed study of long-term outcome in pediatric focal cortical dysplasias was recently published. 18 A comparison of trends between existing pediatric and adult series from different centers is difficult because of potentially divergent catchment areas and inconsistent presurgical, surgical, and postsurgical strategies and assessments. To bridge this gap, we compared data on presurgical and surgical numbers, epileptogenic pathologies, and outcome in pediatric cases to those in adults from a large-volume presurgical/surgical program, thereby reducing the differences in the basic study population and approach to a minimum.…”
mentioning
confidence: 99%
“…Martinez-Lizana et al [49] recently showed that FCD type II detectability on MRI is only slightly higher than FCD type I, which contradicts with previous studies [55] reported a significant difference between types, type II being more frequently identified. There are two theories for this shift of frequency, first one is due to the advances in imaging quality and the second one is due to a selection bias, since the MRIidentified lesions are being selected for epilepsy surgery [49].…”
Section: Neuroimaging Findingsmentioning
confidence: 77%